EDUCATION MORAL FOUNDATIONS IN TEACHINGS OF THE ENGLISH GENIA - Shadmanov K. B. (Journal Park Publishing, 2026)
The paper explores the history of philosophical aspects of educational theory and practice as reflected in the works of prominent educators of the English Enlightenment (late 17th-early 18th centuries). Of particular note in this context is the work entitled "Letters to His Son" by Lord Chesterfield (1694-1773), a prominent British figure, humanist thinker, public figure, statesman, philosopher, historian, and pedagogical follower of the great English philosopher of his time, John Locke. The author shares her understanding of the essence of this issue using the example of this outstanding representative of 18th-century English ethical, philosophical, and pedagogical thought.
Keywords: Morality, education, educational-philosophical, thought, reflection, letter, experience, advice, intelligence.